Distribution and severity of molar hypomineralisation: trial of a new severity index. Issue 2 (22nd May 2013) - Oliver, Kelly; Messer, Louise B.; Manton, David J.; Kan, Karen; Ng, Fiona; Olsen, Christopher; Sheahan, John; Silva, Margarita; Chawla, Narisha
<x xml:space="preserve">Abstract</x> Background Current molar hypomineralisation (MH) indices do not guide clinicians in management of affected dentitions, and treatment is based on individual judgment. Aim The aims of this study were to describe characteristics of MH and molar incisor hypomineralisation (MIH) and trial the new Molar Hypomineralisation Severity Index (MHSI). Design First permanent molars (FPMs) and permanent incisors (PIs) in 283 affected children were examined for hypomineralisation characteristics [defect colour, location, post‐eruptive breakdown (PEB); restorations placed/replaced/atypical; sensitivity]. The MHSI scores were compared with treatment received (152 children). Results Mean (SD) affected teeth/dentition were as follows: FPMs: 3.2 (1.0) and PIs: 1.6 (1.6). Affected FPMs showed no arch or quadrant predilection; maxillary central PIs were affected particularly. As affected FPMs/dentition increased, MIH diagnoses also increased (P = 0.009). Among FPMs, defects most prevalent were brown (47%) and cuspal (74%); 67% showed PEB. Before study entry, 43% of FPMs had restorations placed/replaced. Among PIs, white defects were common (65%) on smooth surfaces; sensitivity was rare. Affected FPMs received more restorations and extractions than unaffected FPMs (P = 0.0001). As MHSI scores increased, FPM treatments/dentition increased (number, invasiveness). All characteristics were significant in predicting treatment (logistic regression model). Conclusions A spectrum from MH to MIH occurred. The MHSI characteristics were predictive of the treatment of affected FPMs and can guide management.